Restoration of Decreased T Helper 1 and CD8+ T Cell Subsets Is Associated With Regression of Lymphoproliferative Disorders Developed During Methotrexate Treatment - Saito, Shuntaro; Suzuki, Katsuya; Yoshimoto, Keiko; Kaneko, Yuko; Yamaoka, Kunihiro; Shimizu, Takayuki; Mori, Takehiko; Okamoto, Shinichiro; Kameyama, Kaori; Amano, Koichi; Tamaru, Jun-ichi; Tokuhira, Michihide; et al. (Frontiers in Immunology, 2018)
Background Lymphoproliferative disorder (LPD), including malignant lymphoma, is a relatively rare but life-threatening complication in RA patients under methotrexate (MTX) therapy. Spontaneous regression of LPD after MTX withdrawal is regarded as a distinct characteristic in part of such LPDs. Objective The present study aimed to investigate the immunological difference in regressive LPD and persistent LPD. Methods We studied RA patients who developed LPD during MTX administration (n = 35) and clinically matched controls (n = 35). The time of MTX cessation was defined as week 0, and LPD patients were divided into two groups according to LPD status at week 12: regressive group (n = 22) and persistent group (n = 13). Flow cytometric analysis of whole blood samples and serum cytokine assays were conducted for LPD (n = 10) and control patients (n = 10) at weeks 0, 4, and 12. Results There was a significant decrease in peripheral lymphocytes and the proportion of T helper 1 cells (Th1 cells), effector memory CD8+ T cells (EMCD8+ T) and Epstein–Barr virus (EBV)-specific CD8+ T cells at the time of LPD diagnosis, and a significant increase after MTX cessation was observed in the regressive group but not in the persistent group. The expansion of Th1 cells and EMCD8+ T cells significantly correlated with an increase in serum interferon (IFN)-γ concentration. Conclusion Changes in Th1 cells, EMCD8+ T cells and EBV-specific CD8+ T cells, which coincided with an increase in IFN-γ, were significantly different between regressive LPD and persistent LPD after MTX cessation.